Linking Productivity and Competitive Advantage: The Mediation of Quality Results - Yangailo, Tryson (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Most studies have shown that there is a significant relationship between productivity and competitive advantage, but none have attempted to include a contingency variable to provide more insight into the nature of this relationship. To fill this gap, this study was conducted to empirically verify this relationship by including 'quality results' as a contingency variable. Design/methodology/Approach: Quantitative research approach was employed and primary data was collected from TAZARA management employees. Model fit, reliability and validity were tested using regression analysis, factor analysis and principal component analysis using Jamovi software. Findings: The results show that there is a positive and significant relationship between productivity and competitive advantage, and between quality results and competitive advantage. The results also show that quality results partially mediate the relationship between productivity and competitive advantage. Practical implications: The study provides insights on the nature of the relationship between productivity and competitive advantage. The study proves that quality results is critical to improving and sustaining productivity to promote competitiveness in an organisation. As organisations relentlessly seek to maintain and gain competitiveness through productivity, managers and employees need to understand how quality results can be integrated into all operations.